kualifikasi guru SD dan problematikanya - ananda, rizki; indah cahyani, putri; tanjung, imawati; narlis, wella apri; juliani, riska (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study focuses on analyzing the qualifications of elementary school teachers in Indonesia and the various challenges they face in practice. Teacher qualifications play a vital role in ensuring the quality of learning and the success of students in achieving learning competencies. Although the government has established minimum academic qualification standards for teachers, there remains a significant gap between policy and practical implementation in the field. This research employs a descriptive qualitative method with a literature review approach as the basis for data collection and analysis. The findings reveal that many elementary school teachers have yet to meet the academic and professional qualifications as mandated by the Teacher and Lecturer Law. The challenges identified include limited access to further education, unequal distribution of teachers, lack of continuous professional development, and heavy administrative workloads. Based on these findings, the study recommends the implementation of more concrete affirmative policies to promote equitable improvement in teacher qualifications, as well as the strengthening of ongoing teacher coaching and supervision systems in elementary schools.